Effective leadership styles in the Millennial Generation and Generation Z in Bima City facing the Society 5.0 Era - Mawar Hidayanti; Fani Fitriani (Pustaka Digital Indonesia, 2025)
This study aims to analyze the leadership styles that are most suitable for millennials and Generation Z, focusing on three leadership styles: Transformational Leadership (X1), Servant Leadership (X2), and Ethical Leadership (X3). The dependent variable in this study is Motivation (Y). This research is descriptive as it aims to examine and analyze the phenomena or issues that arise within a specific context. The sample used in this study consists of MSME actors in the City of Bima, who are part of the millennial and Generation Z groups. These two generations have distinct characteristics, and understanding how different leadership styles affect them is crucial for improving motivation and productivity in the business environment. The findings reveal that the most suitable leadership style for millennials, based on the average score order, is Servant Leadership (86.55%), followed by Ethical Leadership (86.43%), and Transformational Leadership (85.27%). This suggests that millennials value a leadership approach that focuses on serving and empowering others. Meanwhile, for Generation Z, the most suitable leadership style, based on the average score order, is Ethical Leadership (93.82%), followed by Transformational Leadership (86.62%), and Servant Leadership (83.27%). This indicates that Generation Z places a high value on ethical considerations and integrity in leadership. Overall, this study provides valuable insights into how different leadership styles influence the motivation of millennials and Generation Z. It highlights the need for MSME leaders to adapt their leadership styles according to the generational characteristics of their employees to enhance motivation and drive success in the business context of Bima City.